Theoretical and Experimental Studies of Epidermal Heat Flux Sensors for Measurements of Core Body Temperature. Issue 1 (7th May 2015) - Zhang, Yihui; Chad Webb, Richard; Luo, Hongying; Xue, Yeguang; Kurniawan, Jonas; Cho, Nam Heon; Krishnan, Siddharth; Li, Yuhang; Huang, Yonggang; Rogers, John A.
Abstract : Long‐term, continuous measurement of core body temperature is of high interest, due to the widespread use of this parameter as a key biomedical signal for clinical judgment and patient management. Traditional approaches rely on devices or instruments in rigid and planar forms, not readily amenable to intimate or conformable integration with soft, curvilinear, time‐dynamic, surfaces of the skin. Here, materials and mechanics designs for differential temperature sensors are presented which can attach softly and reversibly onto the skin surface, and also sustain high levels of deformation (e.g., bending, twisting, and stretching). A theoretical approach, together with a modeling algorithm, yields core body temperature from multiple differential measurements from temperature sensors separated by different effective distances from the skin. The sensitivity, accuracy, and response time are analyzed by finite element analyses (FEA) to provide guidelines for relationships between sensor design and performance. Four sets of experiments on multiple devices with different dimensions and under different convection conditions illustrate the key features of the technology and the analysis approach. Finally, results indicate that thermally insulating materials with cellular structures offer advantages in reducing the response time and increasing the accuracy, while improving the mechanics and breathability. Abstract : Theoretical approaches, modeling algorithms, materials, and device designs are introduced for noninvasive measurement of core body temperature by using multiple differential temperature sensors that attach intimately onto skin surfaces. Systematic studies of sensitivity, accuracy, and response time include results from analytical models, numerical calculations, and experimental measurement. These findings have potential use in long‐term, continuous monitoring of core body temperature.